2009
DOI: 10.3851/imp1467
|View full text |Cite
|
Sign up to set email alerts
|

Herpesviridae and novel inhibitors

Abstract: Herpesviridae comprises a large family of double-stranded DNA viruses that infect both animals and humans. Eight herpesviruses are known to infect humans: herpes simplex virus type-1 and -2, varicella zoster virus, human cytomegalovirus, Epstein-Barr virus, human herpesvirus 6 type-A and -B, human herpesvirus type-7 and -8 or Kaposi's sarcoma virus. Despite the fact that the past two decades have been evolutionary in the development of antiviral agents, therapeutic choices are restricted by limited efficacy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 113 publications
0
19
0
2
Order By: Relevance
“…We showed that luteolin could inhibit the expression of viral lytic proteins (Figures 2 and 3) Although EBV has been reported to be closely associated with many human diseases, including cancers, the development of anti-EBV therapies has been insignificant compared to that for HIV infections. In the past, some compounds against other herpesviruses have been tested against EBV (Siakallis et al, 2009). They may be divided into two major categories, those that interfere with virus-encoded enzymes important for virus production and those that interfere with cellular process required for virus production.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that luteolin could inhibit the expression of viral lytic proteins (Figures 2 and 3) Although EBV has been reported to be closely associated with many human diseases, including cancers, the development of anti-EBV therapies has been insignificant compared to that for HIV infections. In the past, some compounds against other herpesviruses have been tested against EBV (Siakallis et al, 2009). They may be divided into two major categories, those that interfere with virus-encoded enzymes important for virus production and those that interfere with cellular process required for virus production.…”
Section: Discussionmentioning
confidence: 99%
“…However, over the past few years, the long-term usage of these antiviral agents led to the emergence of nucleoside-analogue-resistant herpesvirus strains, resulting in ineffective conventional therapies (reviewed in Ref. [61]). Additional antiherpetic treatments, such as various antisense-mediated strategies, are therefore under development, in order to specifically knockdown expression of some viral proteins.…”
Section: Ie4 and Its Homologues As Alternative Targets In Antiherpetimentioning
confidence: 99%
“…Benzimidazole derivatives possess a wide range of pharmacological actions such as analgesic, anti-inflammatory, anti-ulcer, anthelmintics, anti-neoplastic, antifungal, antiviral, anti-histaminic and anti-diabetic (Mohamed et al 2006;Sondhi et al 2006;Achar et al 2010;Narasimhan et al 2012;Gao et al 2007;Siakallis et al 2009). …”
Section: Introductionmentioning
confidence: 98%